TPS Type Cooperative Learning Model Based on PBL: Implementation and Influence on Mathematics Learning - Amiman, Regita; Tuerah, Philoteus E. A.; Kaunang , Derel F. (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2024)
Students' problem-solving abilities in solving mathematics story problems could be much higher. Innovation and special studies are needed regarding learning models that can improve problem-solving abilities. This research aims to determine the differences in the test results of students' mathematical problem-solving abilities in solving story problems taught using the think pair share type cooperative learning model with the problem-based learning approach and the results of tests of students' mathematical problem-solving abilities taught using the conventional model on cube and block material. The subjects of this research are class VIIIA, which is taught using a think pair share type cooperative learning model with a problem-based learning approach, and class VIIIB, which uses a conventional learning model. The two classes are homogeneous or equal. The data in this study were taken from the pre-test and post-test results from both classes. Thus, the test results of students' ability to solve mathematical problems to solve story problems are better using the think pair share type cooperative learning model with a problem-based learning approach than the conventional learning model using cube and block material.